Adrenergic Stress Protection of Human iPS Cell-Derived Cardiomyocytes by Fast Kv7.1 Recycling - Piccini, Ilaria; Fehrmann, Edda; Frank, Stefan; Müller, Frank U.; Greber, Boris; Seebohm, Guiscard (Frontiers in Physiology, 2017)
The fight-or-flight response, a physiological acute stress reaction, involves positive chronotropic and inotropic effects on heart muscle cells mediated through β-adrenoceptor activation. Increased systolic calcium is required to enable stronger heart contractions whereas elevated potassium currents are to limit the duration of the action potentials and prevent arrhythmia. The latter effect is accomplished by an increased functional activity of the Kv7.1 channel encoded by KCNQ1. Current knowledge, however, does not sufficiently explain the full extent of rapid Kv7.1 activation and may hence be incomplete. Using inducible genetic KCNQ1 complementation in KCNQ1-deficient human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs), we here reinvestigate the functional role of Kv7.1 in adapting human CMs to adrenergic stress. Under baseline conditions, Kv7.1 was barely detectable at the plasma membrane of hiPSC-CMs, yet it fully protected these from adrenergic stress-induced beat-to-beat variability of repolarization and torsade des pointes-like arrhythmia. Furthermore, isoprenaline treatment increased field potential durations specifically in KCNQ1-deficient CMs to cause these adverse macroscopic effects. Mechanistically, we find that the protective action by Kv7.1 resides in a rapid translocation of channel proteins from intracellular stores to the plasma membrane, induced by adrenergic signaling. Gene silencing experiments targeting RAB GTPases, mediators of intracellular vesicle trafficking, showed that fast Kv7.1 recycling under acute stress conditions is RAB4A-dependent. Our data reveal a key mechanism underlying the rapid adaptation of human cardiomyocytes to adrenergic stress. These findings moreover aid to the understanding of disease pathology in long QT syndrome and bear important implications for safety pharmacological screening.